Cleaning practices and cleaning products in nurseries and schools: to what extent can they impact indoor air quality?. (29th August 2015) - Wei, W.; Boumier, J.; Wyart, G.; Ramalho, O.; Mandin, C.
Abstract: In the framework of a nationwide survey on indoor air quality conducted from September 2009 to June 2011 in 310 nurseries, kindergartens, and elementary schools in all regions of France, cleaning practices and products were described through an extensive questionnaire completed on‐site by expert building inspectors. The questionnaire included the cleaning frequencies and periods, cleaning techniques, whether windows were open during cleaning, and the commercial names of the products used. Analysis of the questionnaire responses showed that cleaning was generally performed daily for furniture and floors. It was performed mostly in the evening with wet mopping and with one or more windows open. Five hundred eighty‐four different cleaning products were listed, among which 218 safety data sheets (SDSs) were available and analyzed. One hundred fifty‐two chemical substances were identified in the SDSs. The typical substances in cleaning products included alcohols, chlorides, terpenes, aldehydes, and ethers; more than half of them are irritants. Two endocrine disruptors, 2‐phenylphenol and Galaxolide, were identified in two cleaning products used every day to clean the floors, in seven kindergartens and in a nursery respectively. Eleven reactive substances containing C=C double bonds, mostly terpenes, were identified in a wide variety of cleaning products.